1998
DOI: 10.1021/es9711167
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Oxidizing Scrubbers for Odor Control

Abstract: In an oxidizing scrubber for odor control, the odorant is absorbed in a scrubber and must be oxidized to allow steadystate operation. The rate of absorption depends on the Henry's law coefficient, the gas-and liquid-phase mass transfer coefficients, and the rate of the oxidation reaction. The effect of a liquid-phase reaction on the liquid-phase mass transfer is often expressed in terms of an enhancement factor. Pseudo-first-order reaction rates were estimated for chlorination reactions for selected odorants. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 6 publications
0
22
0
Order By: Relevance
“…Reaction rates ranging from 4 × 10 4 to 3 × 10 8 (L/mol/sec) are required to achieve rapid removal in wet scrubbers. 4 Although no specific kinetic data are available for the VOCs reported in this work, benzaldehyde, a representative aldehyde previously reported in rendering emissions, has a reported reaction rate of less than 3 × 10 -4 (L/mol/sec at pH 8) with ClO 2 , compared with 5 × 10 5 L/mol/sec (pH 8) for 2-methyl-1-propanethiol. 6 Wet scrubber simulations resulted in removal efficiencies ranging from 10 to 15% for methanethiol and 50-70% for butanal (i.e., mass transfer Table 5.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Reaction rates ranging from 4 × 10 4 to 3 × 10 8 (L/mol/sec) are required to achieve rapid removal in wet scrubbers. 4 Although no specific kinetic data are available for the VOCs reported in this work, benzaldehyde, a representative aldehyde previously reported in rendering emissions, has a reported reaction rate of less than 3 × 10 -4 (L/mol/sec at pH 8) with ClO 2 , compared with 5 × 10 5 L/mol/sec (pH 8) for 2-methyl-1-propanethiol. 6 Wet scrubber simulations resulted in removal efficiencies ranging from 10 to 15% for methanethiol and 50-70% for butanal (i.e., mass transfer Table 5.…”
Section: Discussionmentioning
confidence: 84%
“…However, kinetic data specific to the VOCs generated in the rendering industry are lacking, without which optimal scrubber design is impractical. 4 Kinetic data suggest that typical oxidizing agents used in wet scrubbers (e.g., ClO 2 and ozone) do not react or react slowly with many of the VOCs in rendering plant waste gases. 5,6 Reaction rates ranging from 4 × 10 4 to 3 × 10 8 (L/mol/sec) are reportedly required to achieve rapid removal in wet scrubbers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is a general lack of kinetic data specific for the VOCs generated in the rendering industry, without which optimal scrubber design is impractical. 3 Kinetic data indicate that typical oxidizing agents used in wet scrubbers (eg ClO 2 and ozone or O 3 ) do not react or react slowly with many of the compounds in rendering plant waste gases. 4 -6 Reaction rate constants ranging from 4 × 10 4 to 3 × 10 8 (L mol −1 s −1 ) are reportedly required to achieve rapid removal in wet scrubbers.…”
Section: Introductionmentioning
confidence: 99%
“…4 -6 Reaction rate constants ranging from 4 × 10 4 to 3 × 10 8 (L mol −1 s −1 ) are reportedly required to achieve rapid removal in wet scrubbers. 3 Recent kinetic analysis indicated that ClO 2 does not react with hexanal and 2-methylbutanal over a wide range of pH and temperatures. 5 Similarly, ozone rapidly reacts with reduced sulfur compounds (eg…”
Section: Introductionmentioning
confidence: 99%